Paths to victory : detailed insurgency case studies - Paul, Christopher, 1971-; Clarke, Colin P.; Grill, Beth; Dunigan, Molly (Research report (Rand Corporation), 2013)
In-depth case studies of 41 insurgencies since World War II provide evidence to answer a perennial question in strategic discussions of counterinsurgency: When a country is threatened by an insurgency, what efforts give its government the best chance of prevailing? Each case study breaks the conflict into phases and examines the factors and practices that led to the outcome (insurgent win, counterinsurgent win, or a mixed outcome favoring one side or the other). Detailed analyses of the cases, supplemented by data on 30 previously conducted insurgency case studies (and thus covering all 71 historical insurgencies worldwide since World War II), can be found in the companion volume, Paths to Victory: Lessons from Modern Insurgencies. Collectively, the 71 cases span a vast geographic range (South America, Africa, the Balkans, Central Asia, and the Far East) and include examples of governments that attempted to fight the tide of history -- that is, to quell an anticolonial rebellion or uprisings against apartheid.